Women offenders' narratives of violent crime - Africa, Adelene (Department of Psychology, 2014)
This study addressed this lacuna in the research literature by examining the subjective accounts of women incarcerated for violent crime. By locating itself within a postructuralist framework, this study investigated the meaning which women attributed to their perpetration. It examined the identities which women posited and analysed how they either took up or rejected stereotypical gendered norms.